Pengembangan Wisata Embung Berbasis Mitigasi Bencana pada Embung Setumpeng Desa Gentungan, Mojogedang, Karanganyar - Susatio, Raja; Matin, Hashfi Hawali Abdul; Rachmawati, Siti; Setyono , Prabang; Sunarhadi, Muhammad Amin; Kusumaningrum, Lia (Jurnal Ilmiah MTG, 2025)
Setumpeng Reservoir in Gentungan Village, Mojogedang Subdistrict, Karanganyar Regency was a lively tourism spot. Unfortunately, Covid-19 pandemic made the tourism activity in this area to cease indefinitely. As the tourism activity ceased, the reservoir became neglected. In the near future, Gentungan Village plans to redevelop Setumpeng Reservoir as tourist spot once again. Nevertheless, the possibility of disaster in the area pushes the necessities of planning based on disaster mitigation and reduction. This study aims to create a hazard map to support the sustainable development of Setumpeng Reservoir tourism spot. The method used in this research are field survey to identify potential hazard in the area directly. Hazard that was found in Setumpeng Reservoir area reservoir failure and landslides. Area with high hazard zone is located in downstream of reservoir as this area would face the direct impact of reservoir failures. Area with medium hazard zone can be found in the south of the reservoir that only face small scale landslides. The last area of low hazard zone located in the north of the reservoir as it doesn’t face neither reservoir failure nor landslides. Yet even the area is relatively safe, further study is necessary as it’s a paddy field. A study regarding foundation and building stability is a must.